Pengaruh Persepsi Atas Nomor Izin Edar BPOM, Label Halal, Kualitas Produk, Harga Terhadap Kepercayaan Pelanggan & Persepsi Nilai Pelanggan Serta Dampaknya Pada Minat Beli Kosmetik Import - Mutiara Januari; Triyono Arief Wahyudi (STREAMING, 2025)
The objective of this research is to examine the influence of perceived : NIE BPOM, halal label, product quality and price on customer's trust and customer's perceived value and its impact on purchase intention of imported cosmetic products. The result of this research are (1) perceived NIE BPOM have positive and insignificant influence to customer's trust, (2) perceived label of halal have positive and significant influence to customer trust, (3) perceived quality has positive and significant influence to trust (5) perceived of NIE BPOM has a positive and significant influence on perception of customer value, (6) perceived halal label has a negative and significant influence on the perception of customer value , (7) perceived quality has a positive and significant influence on the perception of customer value, (8) perceived price has a positive and significant impact on customer perceptions, (9) Customer’s trust has a positive and significant effect on purchase intention, (10) customer perceived value has a positive and significant impact ad buying interest.